Varieties of Activist Experience: Civil Society in South Asia. (Governance, Conflict, and Civic Action 3) - Gellner, D (SAGE Publications, 2010)
Includes 'Introduction: Making Civil Society in South Asia' (pp 1-14) and Chapter 6 (with MK Karki) 'Surveying Activists in Nepal' (pp 131-156)